Prunus Persica - Joel Simon. M, Christopher; Roy, Anitha; D, Revathi.; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Widely popular for their sweet, juicy fruits and beautiful blossoms, peach trees are actually plagued by so many different pests and diseases that they should probably only be planted by the horticulturally dedicated homeowner. A low, broad tree, 15 to 25 feet tall with an equal or greater spread, peach trees form a rounded crown with upwardly reaching branches clothed in three to six-inch-long, dark green, deciduous leaves. The lovely flowers, which appear in April before the new leaves unfold, are available in single, semi-double, and double forms in colors ranging from pure white to deep red and bicolors. The flowers are susceptible to damage by late spring frosts or especially cold winters. The luscious three-inch-diameter fruits mature in July to August. Bright yellow fall color really stands out in many years. Prunus persica grows to 4–10 m (13–33 ft) tall and 6 in. in diameter. The leaves are lanceolate, 7–16 cm (2.8–6.3 in) long, 2–3 cm (0.79–1.18 in) broad, and pinnately veined. The flowers are produced in early spring before the leaves; they are solitary or paired, 2.5–3 cm in diameter, pink, with five petals. The fruit has yellow or whitish flesh, a delicate aroma, and a skin that is either velvety (peaches) or smooth (nectarines) in different cultivars. The flesh is very delicate and easily bruised in some cultivars but is fairly firm in some commercial varieties, especially when green. The single, large seed is red-brown, oval-shaped, approximately 1.3–2 cm long, and is surrounded by a wood-like husk. Peaches, along with cherries, plums, and apricots, are stone fruits (drupes). There are various heirloom varieties, including the Indian peach, which arrives in the latter part of the summer. This review article promotes awareness about the medicinal use of Prunus persica.